Reorganise: building a counter-hegemony through alternative organising - Wilson, Matthew (2024)
Providing a broad exploration into the evoloving cultures of alternative forms of organising, this thesis asks big strategic questions about the future of prefigurative praxis. Drawing on the counter-hegemonic analyses of Stuart Hall, it suggests organisation scholars should move beyond micro-perspectives and begin looking at alternative organising from a conjunctural and cultural perspective.